2019
DOI: 10.1021/jacs.9b06580
|View full text |Cite
|
Sign up to set email alerts
|

Probing Binding Interactions of Cytisine Derivatives to the α4β2 Nicotinic Acetylcholine Receptor

Abstract: Nicotinic acetylcholine receptors (nAChR) are crucial for communication between synapses in the central nervous system. As such they are also implicated in several neuropsychiatric and addictive diseases. Cytisine is a partial agonist of some nAChRs and has been used for smoking cessation. Previous studies have established a binding model for several agonists to several nAChR subtypes. Here, we evaluate the extent to which this model applies to cytisine at the α4β2 nAChR, a subtype known to play a prominent ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 52 publications
5
27
0
Order By: Relevance
“…In the α4β2 complexes, ACh exhibited high mobility, adopting many different binding modes in the agonist binding pocket (Figure 1b). As expected from their more rigid structures and additional cation-π interaction with loop C compared to ACh (Blom et al, 2019), cytisine and 10-methylcytisine showed less mobility, generally remaining in the same orientation throughout the simulation. In the α7 complexes, all agonists exhibited greater positional and conformational variability, regardless of the steric bulk and rigidity of the ligands (Figure 1b).…”
Section: An Arginine Residue In β3 Strand Affects Agonist Selectivitysupporting
confidence: 59%
See 1 more Smart Citation
“…In the α4β2 complexes, ACh exhibited high mobility, adopting many different binding modes in the agonist binding pocket (Figure 1b). As expected from their more rigid structures and additional cation-π interaction with loop C compared to ACh (Blom et al, 2019), cytisine and 10-methylcytisine showed less mobility, generally remaining in the same orientation throughout the simulation. In the α7 complexes, all agonists exhibited greater positional and conformational variability, regardless of the steric bulk and rigidity of the ligands (Figure 1b).…”
Section: An Arginine Residue In β3 Strand Affects Agonist Selectivitysupporting
confidence: 59%
“…Although we have found that the C(10) cytisine variants share the same core-binding interactions as cytisine in the α7 and α4β2 nAChRs ( Figure S1B), these compounds display negligible affinity for the α7 subtype, while retaining selectivity for α4β2 nAChR (Rego-Campello et al, 2018). A recent study, using unnatural amino acid chain substitutions to probe the binding interactions of cytisine and its C(10) variants in the α4β2 nAChR, showed that these substitutions only have a modest effect on interactions with residues in loops C and E, depending on the C (10) substituent's steric bulk or electronic properties (Blom et al, 2019). However, the conservation of these residues in α7 nAChR fails to explain the selectivity of the C(10) variants of cytisine.…”
Section: Introductionmentioning
confidence: 99%
“…4B), Blom et al recently showed that the partial α4β2 nAChR agonist cytisine, a smoking cessation drug, forms an additional cation-π interaction in the agonist binding site compared to nicotine. The authors went on to assess the effect of different cytisine modifications on the binding interactions with mutant cycle analysis and developed a structural model for the interaction, informing future drug development for this receptor (Blom et al 2019). Lynagh et al probed the role of a conserved Arg in the ligand binding site of the glutamate-gated chloride channel (GluCl) in ligand recognition.…”
Section: Nonsense Suppression With Orthogonal Trnas In Xenopus Laevismentioning
confidence: 99%
“…This represents a key advantage over conventional site-directed mutagenesis, which cannot typically alter the H-bonding pattern of the protein backbone. In the context of ion channels, this powerful approach has recently been exploited to assess a variety of aspects, including intra-helical coupling in a potassium channel voltage sensor (Infield et al 2018b), ionic selectivity in ASICs (Lynagh et al 2017a) and ligand binding in nAChRs (Blom et al 2019). Finally, the technique can also incorporate larger side chains with novel functionalities.…”
Section: Nonsense Suppression With Orthogonal Trnas In Xenopus Laevismentioning
confidence: 99%
See 1 more Smart Citation